The Influence of LCD Media through PjBL-STEM on Critical Thinking Skills - Widiyono, Aan; Ghufron, Anik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study investigates the impact of LCD media integrated with Project-Based Learning STEM (PjBL-STEM) on enhancing elementary school science students' critical thinking skills. Despite employing a quantitative approach and true experimental design, further clarification on the practical implementation of PjBL-STEM and the role of LCD media in the learning process would be beneficial. PjBL-STEM engages students in hands-on science projects that promote problem-solving, which is typically essential in elementary-level science curricula. However,